ANALISIS PENGURANGAN BEBAN KEMUDI PADA MEKANISME POWER STEERING - Zulfikar Zulfikar (Jurnal Teknik Mesin, 2004)
Power Steering is ministrant mechanism to decrease the required drive burden at the time of car at a speed of lowering; Moment Park or certain maneuver and will change over to manual drive at full tilt. Style to lessen drive burden obtained with fluid pressure with system of hydraulic awakened by direct moved pump with machine rotation. At the time of high machine rotation awakened by fluid pressure is pump will become to go up, drive burden will become as light as a feather. This not desire and will be arranged by valve relief. Loss of fluid flow friction at hydraulic system will lessen pressure, so that style awakened at drive burden mechanism will become to decrease.